Frontiers in Preparations and Promising Applications of Mesoporous Polydopamine for Cancer Diagnosis and Treatment - Hualin Ma; Jingwen Peng; Jianing Zhang; Li Pan; Jiayi Ouyang; Zimu Li; Baochun Guo; Zhen Wang; Ying Xu; Daizheng Lian; Xiaowei Zeng (MDPI AG, 2022)
Polydopamine (PDA) is a natural melanin derived from marine mussels that has good biocompatibility, biodegradability, and photothermal conversion ability. As a new coating material, it offers a novel way to modify the surface of various substances. The drug loading capacity and encapsulation efficiency of PDA are greatly improved via the use of mesoporous materials. The abundant pore canals on mesoporous polydopamine (MPDA) exhibit a uniquely large surface area, which provides a structural basis for drug delivery. In this review, we systematically summarized the characteristics and manufacturing process of MPDA, introduced its application in the diagnosis and treatment of cancer, and discussed the existing problems in its development and clinical application. This comprehensive review will facilitate further research on MPDA in the fields of medicine including cancer therapy, materials science, and biology.